Node-to-Node Approaching in Wireless Mesh Connectivity - Singh, Madhusudan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights routing protocols for wireless mesh networks (WMNs; IEEE 802.11s). It provides an overview of the wireless networks (history, MANET, family of IEEE 802.11, WMNS, etc.) and routing protocols, such as AODV, DSR, OLSR, etc, and also highlights two resolutions of routing protocols with respect to end-to-end delay, packet delivery ratio and routing overhead in WMNs. Wireless mesh networks have become a hot topic for researcher into the deployment of wireless networks, and they represents the connectivity of mesh networking in IEEE 802.11 amendment in static and ad-hoc networks. Moreover, WMNs have numerous attractive features, such as highly reliable connectivity, easy deployment, self-healing, self-configuring, and flexible network expansion. The book describes two routing mechanisms: novel cluster-based routing protocols (NCBRP), and decentralized hybrid wireless mesh protocol (DHWMP).
Wireless Networks: Overview -- Routing Protocols for Wireless Network -- Novel Cluster Based Routing Protocol (NCBRP) -- Decentralized Hybrid Routing Mechanism for WMNs -- Wireless Mesh Network: Real Time Test-bed -- Future of Wireless Mesh Networks.
Keywords: Telecommunication; Application software; Wireless communication systems; Mobile communication systems; Communications Engineering, Networks; Computer and Information Systems Applications; Wireless and Mobile Communication